Досвіток з півнями і тривогою, або міжчасся як прогалина у тексті буття - Ільницький, Микола (Slavia Occidentalis, 2011)
The paper represents the analysis of the situation of «betweenness» as the existential category, in which the concrete historical moment receives metaphysical dimension.